"It will kill your dreams, your goals, your everything"—Humanitarian migrants, governance through containment and the Italian accommodation system. (April 2022) - Lumley-Sapanski, Audrey
Abstract: While asylum seekers await the outcome of their claims to protection in Italy, they are dispersed to accommodation centers administered by subcontracted non-governmental agencies where they receive reception and integration services. In addition, in line with guidelines from the regional government, social operators regulate migrant behavior and mobility through the use of the use of behavioral regulation, deployed temporalities, and various forms of surveillance. Using the lens of migration governmentality and specifically, containment (Tazzioli and Garelli, 2018), this research explores the impact of these forms of governance on migrant settlement outcomes. I do so through a case study of accommodation centers and migrant experiences within accommodation centers in Turin (Italy) conducted in the winter of 2018 and 2019. Findings suggest that migrants are infantilized through the process, one which provides few opportunities to exert autonomy over self-direction and preferred settlement outcomes. Contained within reception centers without opportunities for external engagement, migrants are prevented from developing social ties or place attachment more generally. Migrants reject their subordinated status, and, exhibit a familiar form of autonomy in the post-reception period—migration, including circular and cross border mobility.